Mango and COVID-19: The impact on and coping of Namdokmai Sithong mango export farmers in Khon Kaen, Thailand during the pandemic of COVID-19 - Sornsena , Patcharaporn; Mikhama , Kanlaya; Borisutdhi, Yos (Forest and Society, 2021)
The pandemic of COVID-19 has had impacts on mango export of farmers and they must have coping strategies to survival. Ban Haet Mango Export Community Enterprise is a leading community enterprise that exports Namdokmai Sithong mango. Since 2007, the enterprise has followed the standards set by the Good Agricultural Practices (GAP) in four season per year, ensuring high quality of their mangoes fit for sales in export and domestic markets. For exporting, sold premium graded to distributors and export to Japan, South Korea and China. A few premium graded and a graded lower were sold in the domestic market by farmer themselves and via middlemen. However, at the end of the year 2019, the COVID-19 epidemic erupted, which later spread across the globe that heavily affected on the mango market of farmers. The severity of the impact was identified in two phases, the 1st period during 10-24 March 2020 and the 2nd period during 25 March - 31 May 2020. It was found that three main partners have suffered and their coping strategies were divided into the following two periods: (1) Impact on members and their coping strategies; The 1st period, can't sell mangoes and they put on hold the harvesting of the produce and diverted manpower for finding new markets. The 2nd period, coordinate domestic marketing channel support with relevant sectors, they were able to sell some of their produce. (2) Impact on the community enterprise and its coping strategies; The 1st period, the enterprise was not able to gather the produce from the members for distribution. They coordinated marketing channel support with relevant sectors. The 2nd period, they could gather some of the produce with price slashed by forty percent for export and fifty percent for domestic market when compared with previous year. (3) Impact on export distributors and their adjustment. The 1st period, they were heavily impacted being unable to buy the produce from the enterprise for export. They looked for ways to buy the produce and distributed it to the international market. The 2nd period, they were able to purchase some of the produce for export and the mangoes were transported throughout the chartered flights.